IDENTIFIKASI DAN ANALISIS ALAT TANGKAP JARING KURAU YANG DIGUNAKAN NELAYAN DI PERAIRAN KABUPATEN BENGKALIS - Isnaniah '; Irwandy Syofyan; Dhoni Armansyah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This studied aims to identified and analyzied the construction and design ofKurau gillnet used by fishermen in the Pambang, Bengkalis. This research usedSurvey method by directly interviewing the fishermen and measuring equipmentused. Result from this research was shown that the net where using multifilamentof material blue with 974.4 m in width 13.9 m in length of nets, according to thenumbers of eye length (mesh length) 5800, the numbers of eye towards the bottom(mesh depth) 83. Ris and buoy rope using the same material was PE(polyethilene) with a length of 480 m. Shortening to the net value of 50.73%. Nethauler tools used at the time of withdrawal of the net was placed on the bow of theship.Keywords : gill net, construction, Bengkalis distric